Studi Penumbuhan Film Tipis Ti1-xCoxO2 dengan Teknik MOCVD Menggunakan Prekursor Titanium (IV) Isopropoxide dan Tris (2,2,6,6-tetramethyl-3, 5-heptanedionato) Cobalt (III) - Horasdia Saragih; Edy Supriyanto; Pepen Arifin; Mohammad Barmawi (Journal of Mathematical and Fundamental Sciences, 2006)
The Ti1-xCoxO2 thin films have been grown by MOCVD technique using titanium (IV) isopropoxide (TTIP) and tris (2,2,6,6-tetramethyl-3, 5-heptanedionato) Cobalt (III) [Co(TMHD)3] powder precursors. The tetrahydrofuran (THF) were used as a solvent to get a Co(TMHD)3 solution. Characteristics of precursor and growth parameters were investigated. The Co concentration in thin films were varied. The room temperature ferromagnetic properties of Ti1-xCoxO2 thin films were obtained. Solubility of Co atom in TiO2 lattice were found at about 11%. The surface morphology of films are homogen and relatively smooth.